2015
DOI: 10.1016/j.ejc.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

On edge-transitive cubic graphs of square-free order

Abstract: a b s t r a c tA regular graph is said to be semisymmetric if it is edge-transitive but not vertex-transitive. In this paper, we give a complete list of connected semisymmetric cubic graph of square-free order, which consists of one single graph of order 210 and four infinite families of such graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Applying Lemmas 6.1-6.4 to the pair (X, Γ C ), we conclude that T = soc(X ) = PSL(2, p) and Γ C is X -arc-transitive, and so Γ is arc-transitive. Moreover, G α ∼ = X B ∼ = Z 2 2 , D 8 or D 16 , where B is a C-orbit and α ∈ B. If X B = X α , then G α ≤ X ; in this case, it is easily shown that Γ is isomorphic to the standard double cover of Γ C , and so Theorem 1.1 (10) occurs.…”
Section: Normal Coversmentioning
confidence: 91%
See 4 more Smart Citations
“…Applying Lemmas 6.1-6.4 to the pair (X, Γ C ), we conclude that T = soc(X ) = PSL(2, p) and Γ C is X -arc-transitive, and so Γ is arc-transitive. Moreover, G α ∼ = X B ∼ = Z 2 2 , D 8 or D 16 , where B is a C-orbit and α ∈ B. If X B = X α , then G α ≤ X ; in this case, it is easily shown that Γ is isomorphic to the standard double cover of Γ C , and so Theorem 1.1 (10) occurs.…”
Section: Normal Coversmentioning
confidence: 91%
“…Since Γ is connected, C fixes each vertex of Γ , and so C = 1 as C ≤ AutΓ , a contradiction. Thus |G αβ | is a divisor of 4, and hence G α ∼ = D 8 or D 16 .…”
Section: Casementioning
confidence: 96%
See 3 more Smart Citations